Mercury Content and Pools in Complex Polycyclic Soils From a Mountainous Area in Galicia (NW Iberian Peninsula) - Antía Gómez-Armesto; Antía Gómez-Armesto; Melissa Méndez-López; Melissa Méndez-López; Andrea Parente-Sendín; Andrea Parente-Sendín; Noemi Calvo-Portela; Noemi Calvo-Portela; Xabier Pontevedra-Pombal; Eduardo García-Rodeja; Flora Alonso-Vega; Flora Alonso-Vega; et al. (Spanish Journal of Soil Science, 2023)
Atmospheric mercury (Hg) usually tends to accumulate in the upper horizons of soils. However, the physico-chemical characteristics of some soils, as well as pedogenetic processes, past climate changes, or soil degradation processes, can lead to a redistribution of mercury through the soil profile. In this work, the presence and accumulation of mercury was studied in three deep polycyclic soils from a mountainous area in NW Iberia Peninsula. The highest total Hg values (HgT) were found in the organic matter-rich O and A horizons of FL and MF profiles (169 and 139 μg kg−1, respectively) and in the illuvial horizon of RV (129.2 μg kg−1), with the latter two samples showing the maximum Hg reservoirs (29.3 and 29.0 mg m−2, respectively). Despite finding the highest Hg content in the surface horizons, considerable Hg reservoirs were also observed in depths higher than 40–50 cm, indicating the importance of taking into account these soil layers when Hg pools are evaluated at a global scale. Based on the mass transfer coefficients, we can rule out the contribution of parent material to the Hg accumulation in most of the horizons, thus indicating that pedogenetic processes are responsible for the Hg redistribution observed along the soil profiles. Finally, by means of principal component analysis (PCA) and stepwise linear regression we could assess the main soil components involved in the Hg accumulation in each soil horizon. Therefore, PC1 (organic matter and low stability Al-hummus complexes) showed a higher influence on the surface horizons, whereas PC2 (reactive Al-Fe complexes and medium-high Al-hummus complexes) and PC4 (crystalline Fe compounds and pHw) were more relevant in the Hg distribution observed in the deepest soil layers.